Variation of growth parameters for density controlled PECVD carbon nanotubes - Toh, Han Cheng (2009)
Carbon Nanotubes (CNTs) has been substantially an interesting topic of research due to its unique properties which is seen as a promising prospect for a variety of applications especially in the area of field emitters. It had been published that this property of CNTs may deteriorate due to the high density of CNTs and hence many methods have been done to reduce the density of CNTs. In this project, the growths of CNTs were done in PECVD system whereby reactive gas such as ammonia and acetylene as carbon feedstock gas was used to supplied into the reactive chamber.Pre-treatment such as annealing and etching was performed on the nickel catalyst film. Variations of these two growth parameters has shown to have direct relation with the density of CNTs. Results of these processes reveals a correlation between annealing and etching conditions with the diameters and densities of these CNTs. Few analysis methods were made on the diameter and density of CNTs for verification of these trends. Raman analysis was also conducted on the samples.